Avaliação de marcadores do estresse oxidativo na nefropatia falciforme em crianças com anemia falciforme do Estado de Minas Gerais - Fabíola Gomes Mendes (2022)
Introduction: Sickle cell disease (SCD) is a very common genetic disorder in Brazil and worldwide, characterized by the presence of hemoglobin S in red blood cells. Sickle cell anemia (SCA) is the most severe form of SCD. Its main feature is the change in red blood cell conformity from normal to sickle shape, resulting in chronic hemolytic anemia and vaso-occlusive episodes. Patients with FA are affected by several clinical manifestations, such as, for example, changes in the kidneys. The pathophysiology of sickle cell nephropathy (SNF) is not very well understood. The first manifestations occur in childhood, including hyposthenuria, glomerular hyperfiltration and albuminuria. Activation of inflammatory mediators, endothelial injury and increased expression of adhesion molecules may occur because of oxidative stress, which is considered a factor in modulating the severity of SCD and, probably, NF. The aim of the study was to evaluate the influence of oxidative stress markers on the occurrence of albuminuria in pediatric patients with SCA. Patients and Methods: This is a cross-sectional study carried out in a cohort of pediatric patients with SCD, screened by the Neonatal Screening Program of Minas Gerais (PTN-MG) and followed up at the Hemocentro de Belo Horizonte of Fundação Hemominas. Genotyping of the rs4880 polymorphism was performed by real-time PCR and measurement of the enzymatic activity of glutathione peroxidase (GPX) by colorimetric test in urine samples. The response variables evaluated were albuminuria and persistent albuminuria, as dichotomous variables (present and absent). Continuous variables were expressed as mean and standard deviation (SD) or median and interquartile range. The normal distribution of continuous variables was verified by the Kolmogorov-Smirnov test. Continuous variables were compared using the unpaired Student's t test or the Mann-Whitney U test. Associations between categorical variables were assessed using two-tailed chi-square or Fisher's exact test. Multivariate analysis was performed using logistic regression. Results: The study population consisted of 344 patients with SCD, 163 female and 181 male. Regarding treatment, 203 (59%) albuminuria patients used hydroxyurea (HU), 31 (9%) HU and chronic transfusion regimen, 3 (0.8%) chronic transfusion regimen and 107 (31.1%) did not made use of these therapeutic modalities. Of the 344 participants, 87 (25.3%) had albuminuria and 32 (9.3%) had persistent albuminuria. Regarding the rs4880 polymorphism, 88 (25.6%) presented the TT genotype, 187 (54.4%) the TC genotype and 69 (20.1%) the CC genotype, however, without significant differences between the groups with and no albuminuria or persistent albuminuria. GPX enzyme activity was measured in samples from 120 patients, 60 females and 60 males. Eighty patients (66.7%) had albuminuria and 32 (26.7%) had persistent albuminuria. There was no association between sex, age, therapy in use and GPX enzyme activity. GPX enzyme activity was lower in participants with persistent albuminuria, however the difference was not significant. There was no correlation between the albumin/creatinine ratio in urine and the activity of the GPX enzyme. In the multivariate analysis, only age remained in the final model. Conclusion: There were no significant differences in the frequency of the genotypes of the polymorphism studied in relation to the presence or absence of albuminuria. In addition, no significant differences were detected in the activity of the GXP enzyme in the urine samples in relation to the presence or absence of albuminuria.